Unique Origin of Skarn at the Ohori Base Metal Deposit, Yamagata Prefecture, NE Japan: C, O and S Isotopic Study. Issue 4 (24th September 2013) - Yokoro, Yu; Hanamuro, Takahiro; Nakashima, Kazuo
Abstract The Ohori ore deposit is one of the Cu–Pb–Zn deposits in the Green Tuff region, NE Japan, and consists of skarn‐type (Kaninomata) and vein‐type (Nakanomata) orebodies. The former has a unique origin because its original calcareous rocks were made by hydrothermal precipitation during Miocene submarine volcanism. Carbon and oxygen isotope ratios of skarn calcite and sulfur isotope ratios of sulfides were measured in and around the deposit. Carbon and oxygen isotope ratios of the skarn calcite are δ13C = −15.51 to −5.1‰, δ18O = +3.6 to +22.5‰. δ13C values are slightly lower than those of the Cretaceous skarn deposits in Japan. These isotope ratios of the Kaninomata skarn show that the original calcareous rocks resemble the present submarine hydrothermal carbonates at the CLAM Site, Okinawa Trough, than Cenozoic limestones, even though some isotopic shifts had occurred during later skarnization. δ34S ratios of the sulfide minerals from the Kaninomata and Nakanomata orebodies are mostly in a narrow range of +4.0 to +7.0‰ and they resemble each other, suggesting the same sulfur origin for the both deposits. The magnetite‐series Tertiary Kaninomatasawa granite is distributed just beneath the skarn layer and has δ34S ratios of +7.5 to 8.1‰. The heavy sulfur isotope ratio of the skarn sulfides may have been affected by the Kaninomatasawa granite.